Бюджетна децентралізація та її вплив на регіональний розвиток в Україні - Університет державної фіскальної служби України; University of the State Fiscal Service of Ukraine (Ірпінь, 2019)
У збірнику розглянуто актуальні питання проведення бюджетної децентралізації в Україні. Представлено зарубіжний досвід бюджетної децентралізації. Визначено сучасний стан фінансування та чинники регіонального розвитку в Україні. The collection deals with topical issues of budget decentralization in Ukraine. The foreign experience of budgetary decentralization is presented. The current state of financing and factors of regional development in Ukraine have been determined.
UDFSU, Institute of Finance, Banking, Department of Finance named after L.L. Tarangula